FRI0551 Evaluation of Change in Anti-Citrullinated Peptide Autoantibody Levels in Clinical Practice and Association with Resource Use. (15th July 2016) - Alemao, E.; Guo, Z.; Iannaccone, C.; Frits, M.; Shadick, N.; Weinblatt, M.
Abstract : Background: Testing for anti-citrullinated peptide antibodies (ACPA) has become standard in RA diagnosis in clinical practice, partly due to improved assay specificity compared with detection techniques for antibodies against RF. 1 ACPA concentration, beyond ACPA positivity, is indicative of more aggressive radiographic progression. 2 However, there is limited information on the association between changes in ACPA levels in clinical practice and resource use measures. Objectives: To evaluate the association of changes in ACPA levels with resource use (durable medical equipment [DME] use/hospitalizations) in clinical practice. Methods: Patients enrolled in the Brigham and Women's Hospital Rheumatoid Arthritis Sequential Study (BRASS) Registry, established in 2003, were analysed. BRASS primarily comprises patients with established RA who were evaluated semi-annually for multiple, clinical patient-reported outcomes and resource utilization parameters. The current analysis is based on patients enrolled in the BRASS registry who had ACPA values at baseline and at follow-up visits. ACPA levels were measured by well-documented and validated ELISAs from Inova Diagnostics (San Diego, CA), until its discontinuation in 2011, and Euro-Diagnostica (distributed by IBL-America, Minneapolis, MN) thereafter. Annual mean ACPA change from baseline (CFB) to 12 months was calculated and categorized as decrease (1+ unit decrease), no change (>–1 to <1 unit change) or increase (1+ unit increase). DME use of canes, wheelchairs, walkers and commodes as well as hospitalizations were assessed every 6 months. Multivariate regression analyses controlling for baseline covariates were conducted to evaluate associations between ACPA CFB and resource use measures defined by DME and hospitalizations. Results: A total of 840 patients (64%) in BRASS had ACPA values at baseline and follow-up and were included in the current analysis. A decrease in ACPA levels was observed in 42.6% (n=358) of patients, 18.1% (n=152) had no change and 39.3% (n=330) had an increase. There were no significant differences in baseline characteristics between the three groups, except for BMI; patients with RA with an increase in ACPA levels had significantly lower BMI at baseline. In univariate analyses, the percentages of patients with DME use were 23.8, 30.5 and 29.8% in the groups with a decrease, no change and an increase in ACPA levels, respectively. Similarly, the percentages of patients with hospitalizations were 13.7, 13.9 and 21.3%, respectively. After controlling for baseline covariates, the odds ratio for DME use over 12 months in patients who had an ACPA decrease (vs increase) was 0.60 (95% CI 0.41, 0.89; p=0.011), and the odds ratio for hospitalization was 0.49 (95% CI 0.32, 0.75; p=0.001; Figure ). Conclusions: A reduction in ACPA levels was associated with a reduction in DME use and hospitalizations. References: Whiting PF, et al. Ann Intern Med 2010;152:456–464; W155–466. Ronnelid J, et al. Ann Rheum Dis 2005;64:1744–9. Disclosure of Interest: E. Alemao Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, Z. Guo Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, C. Iannaccone: None declared, M. Frits: None declared, N. Shadick Grant/research support from: Bristol-Myers Squibb, Crescendo Biosciences, Amgen, UCB, Questcor, M. Weinblatt Grant/research support from: Bristol-Myers Squibb, Crescendo Bioscience, UCB, Amgen, Consultant for: Bristol-Myers Squibb, Crescendo Bioscience, UCB, AbbVie, Roche, Janssen, Pfizer, Lilly, Amgen